In Their Own Words: Teachers' Reflections on Adaptability. Issue 3 (2nd July 2016) - Vaughn, Margaret; Parsons, Seth A.; Burrowbridge, Sarah Cohen; Weesner, Janice; Taylor, Laurel
Abstract : Current research explores adaptability by gathering teachers' reflections on their adaptations. However, the field knows little of what the term adaptability means to teachers who currently teach in today's educational context. In this article, adaptability is discussed from the perspectives of 3 practicing classroom educators, teaching in various contexts (geographic region and grade level). Teachers' voices of adaptability are examined and a definition of adaptability is discussed. Obstacles are presented in these teachers' efforts to adapt their instruction in their respective contexts. Teachers then discussed the ways in which they navigated these obstacles to modify their instruction to fit a variety of learners and experiences despite these constraints.